Reduced prevalence of chronic tubal inflammation in tubal pregnancies after levonorgestrel emergency contraception failure. (31st March 2015) - Li, Cheng; Meng, Chun‐Xia; Sun, Lu‐Lu; Zhao, Wei‐Hong; Zhang, Mei; Zhang, Jian; Cheng, Linan
Abstract: Purpose: The aim of this study was to compare chronic fallopian tubal inflammatory disease and fibrosis between patients with general tubal pregnancy (TP) and TP with levonorgestrel (LNG) emergency contraception (EC) failure. Methods: We retrospectively studied patients with general TP ( n  = 79) and TP following LNG‐EC failure ( n  = 81) within the same conception cycle. Information on the gynecological features of each subject was collected. Pelvic inflammatory disease and associated sequelae were assessed by the serum Chlamydia trachomatis (CT) IgG test, laparoscopic evaluation of tubal damage, and histopathological observation of tube tissues. Chi‐square and Student's t ‐tests were employed to determine the difference between the two groups. Results: Compared with general TP, cases of TP following LNG‐EC failure subjects were less likely to have a history of previous ectopic pregnancy (5.06% vs. 18.52%, p  = 0.009) and adnexal surgery (6.33% vs. 22.22%, p  = 0.010). Patients with TP following LNG‐EC failure were less likely to have pelvic inflammatory disease and associated sequelae than those with general TP, as revealed by positive reaction to anti‐CT IgG (18.18% vs. 35.94%, p  = 0.031), assessment of tubal damage (grade I: 5.06% vs. 17.28%; grade II: 2.53% vs. 11.11%; grade III: 1.27% vs. 6.17%; p  = 0.001), infiltration of chronic inflammatory cells (10.91% vs. 62.50%, p  < 0.001), and positive Masson's staining (7.69% vs. 39.58%; p  < 0.001). Conclusions: Compared with cases of general TP, cases of TP following LNG‐EC failure exhibited reduced rates of CT infection, fallopian tubal inflammation, and/or fibrosis. Copyright © 2015 John Wiley & Sons, Ltd.